2018
DOI: 10.1590/1807-3107bor-2018.vol32.0115
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of RANKL in oral giant cell lesions is predictive of aggressiveness

Abstract: The aim of this study was to evaluate the immunohistochemical expression of receptor activator of nuclear factor kappa-B ligand (RANKL) and of osteoprotegerin (OPG), important proteins correlated with osteoclastogenesis, in central giant cell lesions (CGCL) and peripheral giant cell lesions (PGCL) and to compare their expression with the histological and clinical parameters for quantification of multinucleated giant cells (MGC) and their nuclei, lesion size, and recurrences. Twenty cases of each lesion type we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Twenty studies were mainly associated with pathogenesis and nature of GCLs of jaws [ Table 2 ]. [ 2 3 11 13 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 ] Studies suggested p63 and OCT-4 as the markers that could differentiate between GCT of long bones and GCLs of jaws.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty studies were mainly associated with pathogenesis and nature of GCLs of jaws [ Table 2 ]. [ 2 3 11 13 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 ] Studies suggested p63 and OCT-4 as the markers that could differentiate between GCT of long bones and GCLs of jaws.…”
Section: Resultsmentioning
confidence: 99%
“…It is still uncertain whether PGCL is a discrete entity or peripheral variant of a CGCL. [ 5 10 32 ] The nature of CGCL is still obscure and as mentioned by Ahmed and Dunlap,[ 62 ] its reactive nature has recently been questioned because of its potential aggressive nature, bone destruction, and a high-recurrence rate of 11–35%. Some CGCLs demonstrate aggressive behaviour such as a neoplasm[ 10 48 ] and various speculations have ascertained that perhaps there is a reactive and a neoplastic form of CGCL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on literature data, higher RANKL expression in the central variants is found, which explains their clinical behaviour. [7] Despite being a benign lesion, giant cell granuloma can occur in two clinical subforms -non-aggressive and aggressive. [8] Signs of aggressiveness include rapid growth, pain, tooth mobility, root resorption, cortical bone lysis, and recurrence.…”
Section: Introductionmentioning
confidence: 99%